PATIENT BLOOD MANAGEMENT (PBM) STRATEGIES IN BONE MARROW TRANSPLANTATION UNIT - IMPACT ON PRIMARY OUTCOMES: PBM IN BONE MARROW TRANSPLANTATION - Magalhães Chaves, Ana Vitória; Garcia, Yhasmine Delles Oliveira; Nunes Barroso, Karine Sampaio; Mota Segundo, Hércules Amorim; Facundo de Alencar Araripe, Lara; Mariano de Alencar, Paulo Henrique; Maria de Barros Carlos, Luciana; Barroso Duarte, Fernando (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2024)
Objective: Hematopoietic Stem Cell Transplant (HCT) recipients are among the largest consumers of allogeneic red blood cells and platelets. The impact of Patient Blood Management (PBM) strategies on these recipients is poorly understood. Therefore, we evaluated the PBM strategies and their impact on patients undergoing autologous and allogeneic HCT. Methodology: We conducted a retrospective analysis of 333 patients who underwent HCT at the Bone Marrow Transplant Center of the Walter Cantídio University Hospital (HUWC) from 2018 to 2022. Clinical data were collected from medical records. Statistical analysis was performed using Jamovi software version 2.03, with a statistical significance level of p = 0.05. Results: The mean age of the patients was 45 years, with 51% being male. Of the transplants performed, 63% were autologous. The most common diagnosis was plasma cell neoplasia (36.3%). Restrictive strategies were adopted, and the transfusion parameters during HSCT hospitalization were as follows: Hemoglobin <7g/dL, platelets <50,000/µL in case of bleeding or lumbar puncture, <20,000/µL in the presence of fever or central venous access puncture, and <10,000/µL prophylactically. The transfusion requests consisted of 1 unit of red blood cells and 1 unit of platelet "buffy coat" per administration. During hospitalization, 94.3% of the patients received platelet transfusions, and 50.3% received red blood cells. Patients undergoing allogeneic HCT required more transfusions, experienced more transfusion reactions (24.6%), and had a higher number of deaths during hospitalization (p<0.0001) compared to those undergoing autologous HCT. The most frequent transfusion reactions were allergic (8.7%) and febrile non-hemolytic (15%). The number of red blood cell and platelet transfusions showed a strong (p<0.5) and significant (p<0.01) correlation with the collected volume and engraftment time. There was no correlation between the number of transfusions and age or patient survival after hospital discharge. The number of transfusions during this period did not have a significant impact on survival. However, higher mortality was observed among patients who received more transfusions and those who underwent allogeneic HCT. Conclusion: The implementation of PBM for HCT recipients was associated with a significant reduction in allogeneic red blood cell and platelet transfusions and a reduction in transfusion-related costs, without any negative impact on clinical outcomes.